The western Balkans in Turkish foreign policy in the post cold war period (1990-2021) - Memedi, Deniz (My University, 2021)
This study seeks to examine the Turkish foreign policy in the Western Balkans from the end of the Cold War until the present day (2021). Historically, the Balkan Peninsula has been a region of crucial importance to the Ottoman Empire and, later on, to the modernera Turkey. In addition to the geostrategic importance of the Balkan Peninsula as the only land corridor of Turkey to Europe, other factors such as security, economy, kinship ties, and culture have played decisive role in the active engagement of Turkey in this region. During the Cold War, the expansion of its foreign policy faced limitations as a result of the bipolar nature of the international system. In this period, the foreign policy of Turkey in the Balkan region mainly was passive and static. But, after 1990, a greater space for Turkish active presence and engagement in the Balkan region was created with the transformation of the international order and the transition from a bipolar to a unipolar system led by the United States. In this context, the process of violent disintegration of former Yugoslavia was the first serious test for the Turkish foreign policy. However, Turkey through the diplomacy, participation in military and peacekeeping missions and expression of care of refugees fleeing wars, has achieved to be more engaged in the Western Balkans during 1990's. Meanwhile, the beginning of the 21st century marked a change in its domestic policy. The ruling coalitions of the 1990s came to an end. From 2002 until today, Turkey is led by a single party, the Justice and Development Party (JDP). Despite changes in domestic policy, Turkish foreign policy under JDP continued with its active engagement in the Western Balkans during the first two decades of the 21st century. In this framework, this PhD thesis will assess the following question: “Is foreign policy of Turkey under the leadership of the JDP a continuation of the active policy of the 1990s in the Western Balkans?” It concludes that Turkish foreign policy in the Western Balkans marks a continuation of its active engagement from the beginning of the post-Cold War period to the present day. This means that, during this thirty-year period, Turkey has expanded its scope and taken an active part in all major developments in the Western Balkans, thus abandoning the policy of non-involvement in regional issues that was characteristic during the period of Cold War.

Bu çalışma, Soğuk Savaş'ın sona ermesinden günümüze dek (2021) Türkiye'nin Batı Balkanlar'daki dış politikasını incelemeyi amaçlamaktadır. Tarihsel olarak Balkan Yarımadası, Osmanlı İmparatorluğu ve daha sonra modern Türkiye için hayati öneme sahip bir bölge olmuştur. Türkiye'nin Avrupa'ya tek kara koridoru olan Balkan Yarımadası'nın jeostratejik öneminin yanı sıra, Türkiye'nin bu bölgeye aktif katılımında güvenlik, ekonomi, akrabalık, kültür gibi faktörlerde belirleyici olmuştur. Soğuk Savaş döneminde uluslararası sistemin iki kutuplu yapısı gereği Türkiye, dış politikasını genişletme bağlamında kısıtlarla karşı karşıya kalmıştır. Bu dönemde Türkiye'nin Balkan bölgesindeki dış politikası büyük ölçüde pasif ve durağandı. 1990'dan sonra uluslararası sistemin dönüşümü ve iki kutuplu sistemden ABD'nin başını çektiği tek kutuplu sisteme geçilmesiyle birlikte ise Türkiye'nin Balkan bölgesinde varlık göstermesi ve etkinlik sağlaması için elverişli bir ortam ortaya çıkmıştır. Bu konjonktürde Türkiye'nin dış politikası için ilk ciddi sınav, Yugoslavya'nın şiddet yoluyla gerçekleşen dağılma süreci olmuştur. Aktif diplomasisi, askeri ve barışçıl koruma misyonlarına katılım ve savaşlardan kaçan mültecilere kucak açma politikasıyla Türkiye 1990'lı yıllarda Batı Balkanlar'daki gelişmelerde söz sahibi olmayı başarmıştır. Diğer yandan, 21.yüzyılın başlarında Türkiye'nin iç politikasında bir değişiklik olmuş ve 1990'ların koalisyonlar dönemi sona ererek, 2002'den bugüne dek Türkiye'yi tek parti iktidarı olarak Adalet ve Kalkınma Partisi (AKP) yönetmiştir. İç politikadaki değişikliklere rağmen, Türkiye'nin 1990’larda başlayan Batı Balkanlar'daki angajmanlarını 21.yüzyılın ilk yirmi yılında AKP yönetimi de sürdürmüştür. Bu çerçevede, bu doktora tezinin temel araştırma sorusu, AKP iktidarı döneminde Türkiye'nin Batı Balkanlar’a dönük dış politikası, 1990’lardan itibaren yürütülen aktif dış politikanın bir devamı mıdır? olacaktır. Tez, Türkiye'nin Batı Balkanlar'daki dış politikasının Soğuk Savaş sonrası dönemin başlangıcından günümüze kadar bir devamlılık arz ettiği sonucuna varmaktadır. Bu sonuç, son otuz yıllık dönemde, Türkiye'nin Batı Balkanlar'daki tüm önemli gelişmelerde aktif rol aldığı ve böylelikle Soğuk Savaş döneminde karakteristik olan bölgesel meselelere karışmama politikasından vazgeçtiği anlamına gelir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2021
Keywords: Batı Balkanlar; Türk dış politikası; Soğuk savaş sonrası dönem; Uluslararası ilişkiler; Diplomasi; Western Balkans; Turkish foreign policy; Post - cold war period; International relations; Diplomacy